Development of gyrotrons for fusion with power exceeding 1 MW over a wide frequency range. (5th August 2015) - Kariya, T.; Imai, T.; Minami, R.; Numakura, T.; Eguchi, T.; Kato, T.; Endo, Y.; Ichimura, M.; Shimozuma, T.; Kubo, S.; Takahashi, H.; Yoshimura, Y.; et al.
Abstract: Megawatt-class gyrotrons covering a wide frequency range (14 GHz–300 GHz) are in increasing demand for nuclear fusion. Recent electron cyclotron heating and electron cyclotron current drive experiments highlight a requirement of megawatt-scale gyrotrons at a relatively lower frequency (14–35 GHz) range of some plasma devices, like GAMMA 10/PDX of the University of Tsukuba, QUEST of Kyushu University, NSTX-U of Princeton Plasma Physics Laboratory, and Heliotron J of Kyoto University. Collaborative studies for designing a new 28 GHz/35 GHz dual-frequency gyrotron and a 14 GHz gyrotron have commenced. Operation above 1 MW of 28 GHz/35 GHz dual oscillation was demonstrated experimentally. Further in the design of dual-frequency gyrotron, operations with 2 MW 3 s and 0.4 MW CW (continuous wave) at 28 GHz, and power exceeding 1 MW for 3 s at 34.8 GHz have been shown to be feasible. The 14 GHz gyrotron is expected to operate above 1 MW. We are also developing higher frequency gyrotrons (77–300 GHz). The joint program of National Institute for Fusion Science and the University of Tsukuba developed two new 154 GHz gyrotrons for the large helical device after the demonstration of three 77 GHz gyrotrons. The 154 GHz gyrotrons achieved a maximum output power of 1.25 MW and quasi-CW operation of 0.35 MW for 30 min.